An investigation into the most appropriate prediction method for birth outcomes and maternal morbidity, and the influence of socioeconomic status in a group of preganant women in Khayelitsha, South Africa - Davies, Hilary (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2010.